Caregiver family therapy : empowering families to meet the challenges of aging - Qualls, Sarah Honn (American Psychological Association, 2013)
"Caring for an older family member with physical or cognitive impairments is a difficult, strenuous process. Caregivers often struggle to balance their own needs with those of the care recipient. Their relationships with family, friends, coworkers, and even the care recipient can suffer as well. As a result, family members often seek professional help to guide them through the caregiving process. This book presents Caregiver Family Therapy (CFT), a systems approach to treating families that care for an aging adult. CFT consists of three core stages: (1) Identifying the problem; (2) Structuring caregiver roles; and (3) Ensuring caregiver self-care. Transition stages bridge one core stage to the next, helping caregivers structure care for the older adult, examine the impact of caregiving role structures, and consider broader effects of caregiving. As new challenges arise, the stages are repeated and the CFT process begins anew. Full of rich clinical examples, this book will help therapists and other service providers meet the complex, diverse needs of caregiving families"--Publicity materials. (PsycINFO Database Record (c) 2012 APA, all rights reserved).